Losing My Code: An Autoethnography on Language Attrition - NÃºÃ±ez, Jayrome Lleva (JOLLT Journal of Languages and Language Teaching, 2021)
Learning a new language is one of the privileges that a person can get when moving from one place to another and staying there for a longer time. In this paper, I will discuss my journey that resulted to gradual decline of my L1 (First language), Polillohing Tagalog, which is a variety of the Tagalog language, in the Philippines. The result of migration, acquisition of other languages, and exposure to different speaking environment had led me to continuously decline my first language. Using the auto-ethnographic type of writing a research, I reflected on my experiences which lead me to language attrition. Auto-ethnographic research is when the researcher is the participant of the story narrating his experience on the culture and phenomenon of the researched topic.